Semiconductor nanoparticle composite body, dispersion of semiconductor nanoparticle composite body, semiconductor nanoparticle composite body composition, and cured film of semiconductor nanoparticle composite body
Patent Information
- Application Number
- JP2024204049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-31
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-05-29
AI Technical Summary
【0012】 本発明によれば、高い蛍光量子効率(QY)を保ったまま、極性を有する分散媒に高質量分率で分散させることが可能な半導体ナノ粒子複合体を提供することができる。
Smart Images

Figure 2025032144000009 
Figure 2025032144000010 
Figure 2025032144000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a semiconductor nanoparticle composite, a semiconductor nanoparticle composite dispersion, a semiconductor nanoparticle composite composition, and a semiconductor nanoparticle composite cured film. This application claims priority based on Japanese Patent Application No. 2019-103239 filed on May 31, 2019, and Japanese Patent Application No. 2019-103240 filed on the same day, and incorporates by reference all of the contents of said Japanese Patent Application. [Background technology]
[0002] Semiconductor nanoparticles that are small enough to exhibit the quantum confinement effect have a band gap that depends on the particle size. Excitons formed in the semiconductor nanoparticles by means of photoexcitation, charge injection, etc. recombine to emit photons with energy corresponding to the band gap, so that light emission at a desired wavelength can be obtained by appropriately selecting the composition of the semiconductor nanoparticles and their particle size.
[0003] In the early stages of research into semiconductor nanoparticles, the focus was on elements containing Cd and Pb. However, because Cd and Pb are subject to restrictions such as the Restriction on the Use of Certain Hazardous Substances, research has been focused in recent years on non-Cd- and non-Pb-based semiconductor nanoparticles.
[0004] Attempts have been made to apply semiconductor nanoparticles to various applications, such as displays, biological labeling, and solar cells. In particular, for display applications, semiconductor nanoparticles have begun to be made into films and used as wavelength conversion layers. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-136498 A [Non-patent literature]
[0006] [Non-Patent Document 1] Takashi Jin, "Semiconductor Quantum Dots, Their Synthesis and Applications to Life Sciences," Production and Technology, Vol. 63, No. 2, pp. 58-63, 2011 [Non-Patent Document 2] Fabien Dubois et al, “A Versatile Strategy for Quantum Dot Ligand Exchange” J.AM.CHEM.SOC Vol.129, No.3, p.482-483, 2007 [Non-Patent Document 3] Boon-Kin Pong et al, “Modified Ligand-Exchange for Efficient Solubilization of CdSe / ZnS Quantum Dots in Water: A Procedure Guided by Computational Studies” Langmuir Vol.24, No.10, p.5270-5276, 2008 [Non-Patent Document 4] Samsulida Abd. Rahman et al, “Thiolate-Capped CdSe / ZnS Core-Shell Quantum Dots for the Sensitive Detection of Glucose” Sensors Vol.17, No.7, p.1537, 2017 [Non-Patent Document 5] Whitney Nowak Wenger et al, “Functionalization of Cadmium Selenide Quantum Dots with Poly(ethylene glycol): Ligand Exchange, Surface Coverage, and Dispersion Stability” Langmuir, Vol.33, No.33, pp8239-8245, 2017 Summary of the Invention [Problem to be solved by the invention]
[0007] Semiconductor nanoparticles and semiconductor nanoparticle composites can generally be dispersed in a dispersion medium, prepared as a dispersion liquid, and applied in various fields. In particular, for practical use, it is desirable to disperse them in a dispersion medium with an SP value of 8.5 or more. Semiconductor nanoparticles and semiconductor nanoparticle composites synthesized in a nonpolar dispersion medium are highly hydrophobic and therefore easily dispersible in the nonpolar dispersion medium. However, dispersion in a polar dispersion medium with an SP value of 8.5 or more is difficult.
[0008] It is presumed that semiconductor nanoparticles and semiconductor nanoparticle composites synthesized in non-polar dispersion media have small dipole-dipole forces and hydrogen bonding forces. Therefore, among polar dispersion media with SP values of 8.5 or more, semiconductor nanoparticles can be dispersed in toluene and chloroform, which have small dipole-dipole forces and hydrogen bonding forces, just like semiconductor nanoparticles synthesized in organic solvents. However, these polar dispersion media are highly toxic and therefore not practical.
[0009] Known methods for dispersing semiconductor nanoparticles in polar dispersion media with an SP value of 8.5 or more include the ligand exchange method and the encapsulation method. The ligand exchange method is a method of replacing the ligand contained in the semiconductor nanoparticle composite obtained by binding a ligand to the surface of the semiconductor nanoparticle with a ligand having a hydrophilic group. The semiconductor nanoparticle composite obtained by this method can be dispersed in a polar dispersion medium. However, the semiconductor nanoparticle composites disclosed in Non-Patent Documents 1 to 5 and Patent Document 1 have a problem that the luminous efficiency is reduced, although the semiconductor nanoparticles can be dispersed in a polar dispersion medium. The encapsulation method is a method in which a semiconductor nanoparticle composite obtained by binding a ligand to the surface of a semiconductor nanoparticle is further coated with an amphiphilic polymer. However, when the encapsulation method is performed, the amount of dispersant relative to the semiconductor nanoparticles increases, making it difficult to achieve a high mass fraction of the semiconductor nanoparticles.
[0010] Therefore, in order to solve the above problems, an object of the present invention is to provide a semiconductor nanoparticle composite that can be dispersed at a high mass fraction in a polar dispersion medium while maintaining a high fluorescence quantum efficiency (QY). [Means for solving the problem]
[0011] The semiconductor nanoparticle composite according to the present invention is A semiconductor nanoparticle composite in which two or more types of ligands including an aliphatic thiol ligand and a polar ligand are coordinated to the surface of a semiconductor nanoparticle, the ligand comprises an organic group and a coordinating group; The aliphatic thiol ligand has an aliphatic hydrocarbon group as the organic group and a mercapto group as the coordinating group, The polar ligand comprises a hydrophilic functional group on the organic group, the hydrophilic functional group includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an amino group, an ether bond, an ester bond, and a siloxane bond; the mass ratio of the aliphatic thiol ligand to the polar ligand (aliphatic thiol ligand / polar ligand) is 0.05 to 1.00; A semiconductor nanoparticle composite. In this application, the range indicated by "~" is the range including the numbers on both ends. Effect of the Invention
[0012] According to the present invention, it is possible to provide a semiconductor nanoparticle composite that can be dispersed at a high mass fraction in a polar dispersion medium while maintaining a high fluorescence quantum efficiency (QY). [Brief description of the drawings]
[0013] [Figure 1] 1 is a graph showing the results of 1H-NMR analysis of semiconductor nanoparticle composites in Examples. [Diagram 2] 1 is a graph showing the results of 1H-NMR analysis of the ligands used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] (Semiconductor nanoparticle composite) The semiconductor nanoparticle composite according to the present invention has two or more types of ligands coordinated to the surface of the semiconductor nanoparticle. The semiconductor nanoparticle composite according to the present invention has high light-emitting properties and can be dispersed at a high mass fraction in a dispersion medium or a cured film. In the present invention, the semiconductor nanoparticle composite is a semiconductor nanoparticle composite having light emitting properties. The semiconductor nanoparticle composite of the present invention is a particle that absorbs light of 340 nm to 480 nm and emits light with an emission peak wavelength of 400 nm to 750 nm.
[0015] The full width at half maximum (FWHM) of the emission spectrum of the semiconductor nanoparticle composite is preferably 40 nm or less, more preferably 35 nm or less. When the full width at half maximum of the emission spectrum is in the above range, color mixing can be reduced when the semiconductor nanoparticle composite is applied to a display or the like. The fluorescence quantum efficiency (QY) of the semiconductor nanoparticle composite is preferably 80% or more, more preferably 85% or more. When the fluorescence quantum efficiency of the semiconductor nanoparticle composite is 80% or more, color conversion can be performed more efficiently. In the present invention, the fluorescence quantum efficiency of the semiconductor nanoparticle composite can be measured using a quantum efficiency measurement system.
[0016] -Semiconductor nanoparticles- The semiconductor nanoparticles constituting the semiconductor nanoparticle composite are not particularly limited as long as they satisfy the above-mentioned luminescence characteristics such as the fluorescence quantum efficiency and the half-width, and may be particles made of one type of semiconductor or particles made of two or more different types of semiconductors. In the case of particles made of two or more different types of semiconductors, the semiconductors may form a core-shell structure. For example, the particles may be core-shell type particles having a core containing a group III element and a group V element and a shell containing group II and group VI elements that covers at least a part of the core. Here, the shell may have a plurality of shells made of different compositions, and may have one or more gradient shells in which the ratio of the elements constituting the shell changes in the shell.
[0017] Specific examples of Group III elements include In, Al, and Ga. Specific examples of Group V elements include P, N and As. The composition for forming the core is not particularly limited, but from the viewpoint of light emission characteristics, InP is preferable.
[0018] The Group II element is not particularly limited, but examples thereof include Zn and Mg. Group VI elements include, for example, S, Se, Te and O. The composition forming the shell is not particularly limited, but from the viewpoint of the quantum confinement effect, ZnS, ZnSe, ZnSeS, ZnTeS, ZnTeSe, etc. are preferable. In particular, when Zn element is present on the surface of the semiconductor nanoparticle, the effect of the present invention can be more effectively exhibited.
[0019] In the case where there are multiple shells, it is sufficient that at least one shell of the above-mentioned composition is included. In addition, in the case where there is a gradient type shell in which the ratio of the elements constituting the shell changes within the shell, the shell does not necessarily have to have the composition as indicated in the composition notation. Here, in the present invention, whether the shell covers at least a portion of the core and the element distribution inside the shell can be confirmed by, for example, composition analysis using energy dispersive X-ray spectroscopy with a transmission electron microscope (TEM-EDX).
[0020] In the present invention, the average particle size of the semiconductor nanoparticles can be measured by calculating the particle size of 10 or more particles in a particle image observed using a transmission electron microscope (TEM) as the equivalent circle diameter (Heywood diameter). From the viewpoint of luminescence characteristics, it is preferable that the particle size distribution is narrow, and it is preferable that the coefficient of variation of the particle size is 15% or less. Here, the coefficient of variation is defined as "coefficient of variation = standard deviation of particle size / average particle size". A coefficient of variation of 15% or less is an indicator that semiconductor nanoparticles with a narrower particle size distribution have been obtained.
[0021] An example of a method for producing semiconductor nanoparticles will be disclosed below. The cores of the semiconductor nanoparticles can be formed by mixing a Group III precursor, a Group V precursor, and, if necessary, an additive in a solvent and heating the resulting precursor mixture. Coordinating and non-coordinating solvents are used, including 1-octadecene, hexadecane, squalane, oleylamine, trioctylphosphine, and trioctylphosphine oxide. Group III precursors include, but are not limited to, acetates, carboxylates, and halides containing the Group III elements. Group V precursors include, but are not limited to, organic compounds and gases containing the above-mentioned Group V elements. When the precursor is a gas, the core can be formed by injecting the gas into a precursor mixture containing other gases and reacting them.
[0022] The semiconductor nanoparticles may contain one or more elements other than Group III and Group V elements as long as the effects of the present invention are not impaired. In this case, a precursor of the element may be added during core formation. Examples of additives include dispersants such as carboxylic acids, amines, thiols, phosphines, phosphine oxides, phosphinic acids, and phosphonic acids, but are not limited thereto. The dispersant can also serve as a solvent. After the core of the semiconductor nanoparticle is formed, a halide can be added as necessary to improve the light emitting properties of the semiconductor nanoparticle.
[0023] In one embodiment, a metal precursor solution in which an In precursor and, if necessary, a dispersant are added to a solvent is mixed under vacuum, and the mixture is heated at 100°C to 300°C for 6 to 24 hours, after which a P precursor is added and the mixture is heated at 200°C to 400°C for 3 to 60 minutes, and then cooled. A halogen precursor is further added and the mixture is heated at 25°C to 300°C, preferably 100°C to 300°C, more preferably 150°C to 280°C, to obtain a core particle dispersion liquid containing core particles.
[0024] By adding a shell-forming precursor to the synthesized core particle dispersion, the semiconductor nanoparticles can adopt a core-shell structure, thereby improving the fluorescence quantum efficiency (QY) and stability. The elements that make up the shell are thought to form an alloy, heterostructure, or amorphous structure on the surface of the core particle, but it is also possible that some of them migrate to the inside of the core particle by diffusion.
[0025] The added shell-forming element is mainly present near the surface of the core particle and plays a role in protecting the semiconductor nanoparticle from external factors. In the core-shell structure of the semiconductor nanoparticle, the shell preferably covers at least a part of the core, and more preferably uniformly covers the entire surface of the core particle.
[0026] In one embodiment, a Zn precursor and a Se precursor are added to the aforementioned core particle dispersion liquid, and then the mixture is heated at 150° C. to 300° C., preferably 180° C. to 250° C., and then a Zn precursor and a S precursor are added, and the mixture is heated at 200° C. to 400° C., preferably 250° C. to 350° C. This allows core-shell type semiconductor nanoparticles to be obtained. Here, although not particularly limited, examples of Zn precursors that can be used include carboxylates such as zinc acetate, zinc propionate, and zinc myristate, halides such as zinc chloride and zinc bromide, and organic salts such as diethylzinc. As the Se precursor, phosphine selenides such as tributylphosphine selenide, trioctylphosphine selenide, and tris(trimethylsilyl)phosphine selenide, selenols such as benzeneselenol and selenocysteine, and selenium / octadecene solutions can be used. As the S precursor, phosphine sulfides such as tributylphosphine sulfide, trioctylphosphine sulfide, and tris(trimethylsilyl)phosphine sulfide, thiols such as octanethiol, dodecanethiol, and octadecanethiol, and sulfur / octadecene solution can be used. The shell precursors may be mixed in advance and added all at once or in multiple portions, or each may be added separately all at once or in multiple portions. When the shell precursors are added in multiple portions, each addition may be heated at a different temperature.
[0027] In the present invention, the method for producing semiconductor nanoparticles is not particularly limited, and in addition to the methods described above, any method may be used, including conventional production methods such as the hot injection method, the homogeneous solvent method, the reverse micelle method, and the CVD method.
[0028] -Ligand- In the present invention, the semiconductor nanoparticle composite is a semiconductor nanoparticle having a ligand coordinated to the surface thereof. The term "coordination" used herein means that the ligand chemically affects the surface of the semiconductor nanoparticle. The ligand may be bonded to the surface of the semiconductor nanoparticle by a coordinate bond or any other bonding mode (e.g., a covalent bond, an ionic bond, a hydrogen bond, etc.), or may not necessarily be bonded when at least a portion of the surface of the semiconductor nanoparticle has a ligand.
[0029] In the present invention, the ligand coordinated to the semiconductor nanoparticles is composed of an organic group and a coordinating group. Two or more types of ligands, including an aliphatic thiol ligand and a polar ligand, are coordinated to the surface of the semiconductor nanoparticles. The aliphatic thiol ligand has an organic group that is an aliphatic hydrocarbon group and a coordinating group that is a mercapto group. The polar ligand contains a hydrophilic functional group in the organic group.
[0030] The organic group of the aliphatic thiol ligand is preferably an aliphatic hydrocarbon group having 6 to 14 carbon atoms. The structure of the organic group of the aliphatic thiol ligand may be any of linear, branched, and non-aromatic rings, and high fluorescence quantum efficiency can be obtained by having the carbon number of the organic group in the range of 6 to 14. The aliphatic thiol ligand is preferably one or more selected from the group consisting of hexanethiol, octanethiol, decanethiol, and dodecanethiol. By adopting these ligands as the aliphatic thiol ligand, higher fluorescence quantum efficiency can be obtained. Since the coordinating group of the aliphatic thiol ligand is a mercapto group, the aliphatic thiol ligand can be tightly coordinated to the surface of the semiconductor nanoparticle.
[0031] The polar ligand has a hydrophilic functional group in the organic group. As the hydrophilic functional group, for example, at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an amino group, an ether bond, an ester bond, and a siloxane bond is selected. By having a hydrophilic functional group in the organic group of the polar ligand, dispersion in a polar dispersion medium is possible. In particular, when the organic group of the polar ligand contains an ether bond, high fluorescent quantum efficiency is obtained and dispersion in a wide range of polar dispersion media is possible. If it is dispersible in a wide range of polar dispersion media, when a semiconductor nanoparticle composite in which the ligand is coordinated to the surface of the semiconductor nanoparticle is used in a resin, the reaction between the ligand and the resin hardly occurs, which leads to a wide range of resin selection.
[0032] The coordinating group of the polar ligand is preferably a mercapto group or a carboxyl group, and more preferably a mercapto group, in view of the strength of coordination to the semiconductor nanoparticles.
[0033] The molecular weight of the polar ligand is preferably 50 or more and 600 or less, more preferably 50 or more and 450 or less. By using a ligand having a molecular weight of 600 or less, the size and volume of the semiconductor nanoparticle composite are prevented from increasing, and when the semiconductor nanoparticle composite is applied to a dispersion liquid, a composition, a cured film, etc., it becomes easy to increase the mass fraction of the semiconductor nanoparticle composite relative to these. On the other hand, when the molecular weight is 50 or more, the effect of steric hindrance is fully exerted, and the occurrence of aggregation, etc. can be suppressed. By setting the molecular weight of the polar ligand in the semiconductor nanoparticle composite within the above-mentioned range, the semiconductor nanoparticle composite can be dispersed at a high mass fraction in an organic dispersion medium described below.
[0034] The mass ratio of the aliphatic thiol ligand to the polar ligand (aliphatic thiol ligand / polar ligand) may be 0.05 to 1.00. With the mass ratio in this range, high fluorescence quantum efficiency can be obtained. If the mass ratio of the aliphatic thiol ligand to the polar ligand (aliphatic thiol ligand / polar ligand) exceeds 1.00, it may be difficult to disperse the aliphatic thiol ligand in a polar dispersion medium having an SP value of 8.5 or more. The mass ratio (aliphatic thiol ligand / polar ligand) is more preferably 0.10 to 1.00, and even more preferably 0.20 to 0.80.
[0035] In addition, when the ligands include ligands other than the aliphatic thiol ligand and the polar ligand, the total mass fraction of the aliphatic thiol ligand and the polar ligand with respect to the total ligands is preferably 0.7 or more. By making the mass fraction 0.7 or more, the semiconductor nanoparticle composite can be easily dispersed in a polar dispersion medium, and the fluorescence quantum efficiency can be prevented from decreasing. It is more preferable that the total mass fraction of the aliphatic thiol ligand and the polar ligand with respect to the total ligands is 0.8 or more.
[0036] The mass ratio of the aliphatic thiol ligand and the polar ligand coordinated to the surface of the semiconductor nanoparticle can be quantified using 1H-NMR. The obtained semiconductor nanoparticle complex is dispersed in a heavy solvent, and an electromagnetic wave is applied in a magnetic field to cause 1H nuclear magnetic resonance. The free induction decay signal obtained at this time is subjected to Fourier analysis to obtain a 1H-NMR spectrum. Since the 1H-NMR spectrum gives characteristic signals at positions corresponding to the structure of the ligand species, the type of each ligand is identified and the ratio is calculated from the positions of these signals and the integrated intensity ratio. Examples of heavy solvents include CDCl3, acetone-d6, and N-hexane-D14.
[0037] (Method of Producing Semiconductor Nanoparticle Composite) An example of a method for producing a semiconductor nanoparticle composite will be disclosed below. There is no limitation on the method of coordinating the ligand to the semiconductor nanoparticles, but a ligand exchange method utilizing the coordination power of the ligand can be used. Specifically, the semiconductor nanoparticles in which the organic compound used in the process of producing the semiconductor nanoparticles is coordinated to the surface of the semiconductor nanoparticles are contacted with the target ligand in a liquid phase to obtain a semiconductor nanoparticle composite in which the target ligand is coordinated to the surface of the semiconductor nanoparticles. In this case, a liquid phase reaction using a solvent as described below is usually performed, but if the ligand used is liquid under the reaction conditions, it is also possible to use the ligand itself as the solvent and to adopt a reaction format in which no other solvent is added.
[0038] Furthermore, if a purification step and a redispersion step as described below are carried out before the ligand is coordinated, the desired ligand can be easily coordinated. When a non-coordinating solvent is used during the synthesis of semiconductor nanoparticles, the generation of defects on the surface of the semiconductor nanoparticles when the desired ligand is coordinated can be minimized, and a decrease in the fluorescence quantum efficiency can be prevented.
[0039] In one embodiment, the semiconductor nanoparticle-containing dispersion liquid after the production of the semiconductor nanoparticles is purified and redispersed, and then a solvent containing an aliphatic thiol ligand is added, and a solvent containing a polar ligand is further added, and the mixture is stirred for 1 to 120 minutes at 50° C. to 200° C. in a nitrogen atmosphere to obtain the desired semiconductor nanoparticle composite. The aliphatic thiol ligand and the polar ligand may be added simultaneously.
[0040] The semiconductor nanoparticles and semiconductor nanoparticle composites can be purified as follows. In one embodiment, the semiconductor nanoparticle composites can be precipitated from the dispersion by adding a polarity-reversing solvent such as acetone. The precipitated semiconductor nanoparticle composites can be collected by filtration or centrifugation, while the supernatant containing unreacted starting materials and other impurities can be discarded or reused. The precipitated semiconductor nanoparticle composites can then be washed with additional dispersion medium and dispersed again. This purification process can be repeated, for example, 2-4 times, or until the desired purity is reached. In the present invention, the method for purifying the semiconductor nanoparticle composite is not particularly limited, and in addition to the methods described above, for example, coagulation, liquid-liquid extraction, distillation, electrodeposition, size exclusion chromatography and / or ultrafiltration, or any other method can be used alone or in combination.
[0041] (Semiconductor nanoparticle composite dispersion) The semiconductor nanoparticle composite contained in the semiconductor nanoparticle composite dispersion of the present invention can adopt the configuration of the semiconductor nanoparticle composite of the present invention described above. In the present invention, the state in which the semiconductor nanoparticle composite is dispersed in a dispersion medium refers to a state in which the semiconductor nanoparticle composite does not precipitate or does not remain as visible turbidity (cloudiness) when the semiconductor nanoparticle composite and the dispersion medium are mixed. Note that the semiconductor nanoparticle composite dispersed in the dispersion medium is referred to as a semiconductor nanoparticle composite dispersion.
[0042] The semiconductor nanoparticle composite of the present invention can be dispersed in an organic dispersion medium to form a semiconductor nanoparticle composite dispersion liquid. The semiconductor nanoparticle composite of the present invention can be dispersed in an organic dispersion medium with an SP value of 8.5 or more, an organic dispersion medium with an SP value of 9.0 or more, or an organic dispersion medium with an SP value of 10.0 or more to form a semiconductor nanoparticle composite dispersion liquid. The SP value here is the Hildebrand solubility parameter, which is a value calculated from the Hansen solubility parameter, which can be determined using the values in handbooks, such as “Hansen Solubility Parameters: A User's Handbook”, 2nd Edition, CM Hansen (2007), or the program in Practice (HSPiP) (2nd Edition) provided by Hanson and Abbot et al.
[0043] By setting the mass ratio of the aliphatic thiol ligand to the polar ligand to the aforementioned ratio, it becomes possible to disperse the semiconductor nanoparticle composite in one or more organic dispersion media selected from the group consisting of hexane, acetone, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), isopropyl alcohol (IPA), isobornyl acrylate (IBOA), ethanol, and methanol as the organic dispersion medium. In particular, it becomes possible to select polar organic dispersion media such as alcohols, ketones, esters, glycol ethers, and glycol ether esters as the organic dispersion medium. By dispersing in these organic dispersion media, the semiconductor nanoparticle composite can be used while maintaining its dispersibility when applied to dispersion in a cured film or resin, which will be described later. In particular, PGMEA and PGME are commonly used as dilution solvents in the field of photoresists, and if the semiconductor nanoparticle composite is dispersible in PGMEA and PGME, the semiconductor nanoparticle composite can be widely applied to the photoresist field.
[0044] When the semiconductor nanoparticle composite has the above-mentioned configuration, the semiconductor nanoparticle composite can be dispersed in an organic dispersion medium at a high mass fraction, and as a result, the mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite dispersion can be made 20 mass% or more, further 25 mass% or more, and even 35 mass% or more.
[0045] Furthermore, in the present invention, a monomer can be selected as a dispersion medium for the semiconductor nanoparticle composite dispersion liquid. The monomer is not particularly limited, but is preferably a (meth)acrylic monomer that allows a wide range of applications for the semiconductor nanoparticles. According to the application of the semiconductor nanoparticle composite dispersion, the (meth)acrylic monomer may be selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 3,5,5-trimethylcyclohexanol (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, methoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, methoxytriethylene glycol acrylate, 2-ethylhexyl diglycol acrylate, methoxypolyethylene glycol acrylate, methoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, methoxytriethylene glycol acrylate, 2-ethylhexyl diglycol acrylate, methoxypolyethylene glycol acrylate, methoxyethyl (meth) ... Dipropylene glycol acrylate, phenoxyethyl (meth)acrylate, 2-phenoxydiethylene glycol (meth)acrylate, 2-phenoxypolyethylene glycol (meth)acrylate (n≒2), tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, dicyclopentanyloxyl ether ethyl (meth)acrylate, isobornyloxylethyl (meth)acrylate, adamantyl (meth)acrylate, dimethyladamantyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, benzyl (meth)acrylate, ω-carboxy-polycaprolactone (n≒2) monoacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-phenoxyethyl (meth)acrylate, (2-methyl-2-ethyl-1,The monomer may be selected from (meth)acrylic monomers such as 3-dioxolan-4-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, o-phenylphenol ethoxy (meth)acrylate, dimethylamino (meth)acrylate, diethylamino (meth)acrylate, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, glycidyl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphoric acid, acryloylmorpholine, dimethylacrylamide, dimethylaminopropylacrylamide, isopropylacrylamide, diethylacrylamide, hydroxyethylacrylamide, and N-acryloyloxyethylhexahydrophthalimide. These may be used alone or in combination of two or more. In particular, the acrylic monomer is preferably one or a mixture of two or more selected from lauryl (meth)acrylate and 1,6-hexadiol di(meth)acrylate depending on the application of the semiconductor nanoparticle composite dispersion liquid. As the dispersion medium of the semiconductor nanoparticle composite dispersion liquid, a prepolymer can be selected. Although there is no particular limitation on the prepolymer, examples of the prepolymer include an acrylic resin prepolymer, a silicone resin prepolymer, and an epoxy resin prepolymer.
[0046] The semiconductor nanoparticle composite dispersion of the present invention preferably has a fluorescence quantum efficiency (QY) of 80% or more, more preferably 85% or more. When the semiconductor nanoparticle composite dispersion has a fluorescence quantum efficiency of 80% or more, color conversion can be performed more efficiently. The fluorescence quantum efficiency of the semiconductor nanoparticle composite dispersion can be measured using a quantum efficiency measurement system.
[0047] (Semiconductor nanoparticle composite composition) In the present invention, a monomer or a prepolymer can be selected as the dispersion medium of the semiconductor nanoparticle composite dispersion to form a semiconductor nanoparticle composite composition. The monomer or prepolymer is not particularly limited, but examples thereof include radical polymerizable compounds containing an ethylenically unsaturated bond, siloxane compounds, epoxy compounds, isocyanate compounds, and phenol derivatives. Furthermore, a crosslinking agent may be added to the semiconductor nanoparticle composite composition. The crosslinking agent is selected from polyfunctional (meth)acrylates, polyfunctional silane compounds, polyfunctional amines, polyfunctional carboxylic acids, polyfunctional thiols, polyfunctional alcohols, polyfunctional isocyanates, and the like, depending on the type of monomer in the semiconductor nanoparticle composite composition. Furthermore, the semiconductor nanoparticle composite composition may further contain various organic solvents that do not affect curing, such as aliphatic hydrocarbons such as pentane, hexane, cyclohexane, isohexane, heptane, octane, and petroleum ether, alcohols, ketones, esters, glycol ethers, glycol ether esters, aromatic hydrocarbons such as benzene, toluene, xylene, and mineral spirits, and alkyl halides such as dichloromethane and chloroform. The above organic solvents can be used not only for diluting the semiconductor nanoparticle composite composition, but also as organic dispersion media. That is, it is also possible to disperse the semiconductor nanoparticle composite of the present invention in the above organic solvent to obtain a semiconductor nanoparticle composite dispersion liquid.
[0048] Furthermore, the semiconductor nanoparticle composite composition may contain appropriate initiators, scattering agents, catalysts, binders, surfactants, adhesion promoters, antioxidants, ultraviolet absorbers, anti-aggregation agents, dispersants, and the like, depending on the type of monomer in the semiconductor nanoparticle composite composition. Furthermore, in order to improve the optical properties of the semiconductor nanoparticle composite composition or the semiconductor nanoparticle composite cured film described later, the semiconductor nanoparticle composite composition may contain a scattering agent. The scattering agent is a metal oxide such as titanium oxide or zinc oxide, and the particle size thereof is preferably 100 nm to 500 nm. From the viewpoint of the scattering effect, the particle size of the scattering agent is more preferably 200 nm to 400 nm. The inclusion of a scattering agent increases the absorbance by about two times. The content of the scattering agent is preferably 2 mass % to 30 mass % relative to the composition, and more preferably 5 mass % to 20 mass % from the viewpoint of maintaining the patternability of the composition.
[0049] The configuration of the semiconductor nanoparticle composite of the present invention allows the mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite composition to be 30 mass% or more. By setting the mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite composition to 30 mass% to 95 mass%, the semiconductor nanoparticle composites and semiconductor nanoparticles can be dispersed at a high mass fraction in the cured film described below.
[0050] When the semiconductor nanoparticle composite composition of the present invention is formed into a 10 μm film, the absorbance of the film with respect to light having a wavelength of 450 nm from the normal direction is preferably 1.0 or more, more preferably 1.3 or more, and even more preferably 1.5 or more. This allows efficient absorption of light from a backlight, thereby making it possible to reduce the thickness of the cured film described below and to miniaturize the device to which it is applied.
[0051] (Diluted Composition) The diluted composition is obtained by diluting the aforementioned semiconductor nanoparticle composite composition of the present invention with an organic solvent. The organic solvent for diluting the semiconductor nanoparticle composite composition is not particularly limited, and examples thereof include aliphatic hydrocarbons such as pentane, hexane, cyclohexane, isohexane, heptane, octane, and petroleum ether, alcohols, ketones, esters, glycol ethers, glycol ether esters, aromatic hydrocarbons such as benzene, toluene, xylene, and mineral spirits, and alkyl halides such as dichloromethane and chloroform. Among these, glycol ethers and glycol ether esters are preferred from the viewpoints of solubility in a wide range of resins and uniformity of the coating when applied.
[0052] (Cured film of semiconductor nanoparticle composite) In the present invention, the term "semiconductor nanoparticle composite cured film" refers to a film containing a semiconductor nanoparticle composite and being cured. The semiconductor nanoparticle composite cured film can be obtained by curing the above-mentioned semiconductor nanoparticle composite composition or diluted composition into a film. The semiconductor nanoparticle composite cured film contains semiconductor nanoparticles, ligands coordinated to the surfaces of the semiconductor nanoparticles, and a polymer matrix. The polymer matrix is not particularly limited, and examples thereof include (meth)acrylic resin, silicone resin, epoxy resin, silicone resin, maleic acid resin, butyral resin, polyester resin, melamine resin, phenolic resin, and polyurethane resin. The semiconductor nanoparticle composite cured film may be obtained by curing the above-mentioned semiconductor nanoparticle composite composition. The semiconductor nanoparticle composite cured film may further contain a crosslinking agent.
[0053] The method for curing the film is not particularly limited, and the film can be cured by a curing method suitable for the composition constituting the film, such as heat treatment or ultraviolet treatment. The semiconductor nanoparticles and the ligands coordinated to the surface of the semiconductor nanoparticles contained in the semiconductor nanoparticle composite cured film preferably constitute the semiconductor nanoparticle composite described above. By configuring the semiconductor nanoparticle composite contained in the semiconductor nanoparticle composite cured film of the present invention as described above, it is possible to disperse the semiconductor nanoparticle composite in the cured film at a higher mass fraction. The mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite cured film is preferably 30 mass% or more, and more preferably 40 mass% or more. However, if it is 70 mass% or more, the composition constituting the film becomes less, making it difficult to cure and form the film.
[0054] The semiconductor nanoparticle composite cured film of the present invention contains a high mass fraction of the semiconductor nanoparticle composite, and therefore the absorbance of the semiconductor nanoparticle composite cured film can be increased. When the semiconductor nanoparticle composite cured film has a thickness of 10 μm, the absorbance of the semiconductor nanoparticle composite cured film is preferably 1.0 or more, more preferably 1.3 or more, and even more preferably 1.5 or more, relative to light having a wavelength of 450 nm from the normal direction of the semiconductor nanoparticle composite cured film.
[0055] Furthermore, since the semiconductor nanoparticle composite cured film of the present invention contains a semiconductor nanoparticle composite having high luminescence properties, it is possible to provide a semiconductor nanoparticle composite cured film having high luminescence properties. The fluorescence quantum efficiency of the semiconductor nanoparticle composite cured film is preferably 70% or more, and more preferably 80% or more.
[0056] In order to miniaturize the device to which the semiconductor nanoparticle composite cured film is applied, the thickness of the semiconductor nanoparticle composite cured film is preferably 50 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less.
[0057] (Semiconductor nanoparticle composite patterned film and display element) The semiconductor nanoparticle composite patterned film can be obtained by forming the above-mentioned semiconductor nanoparticle composite composition or dilution composition into a film pattern. The method for forming the semiconductor nanoparticle composite composition and dilution composition into a pattern is not particularly limited, and examples thereof include spin coating, bar coating, inkjet, screen printing, and photolithography. The display element uses the semiconductor nanoparticle composite patterned film. For example, by using the semiconductor nanoparticle composite patterned film as a wavelength conversion layer, a display element having excellent fluorescent quantum efficiency can be provided.
[0058] The semiconductor nanoparticle composite dispersion of the present invention has the following configuration. (1) A dispersion in which a semiconductor nanoparticle composite is dispersed in an organic dispersion medium, The semiconductor nanoparticle composite comprises two or more ligands including an aliphatic thiol ligand and a polar ligand, and a semiconductor nanoparticle having the ligands coordinated to the surface thereof; the ligand comprises an organic group and a coordinating group; The polar ligand comprises a hydrophilic functional group on the organic group, The SP value of the organic dispersion medium is 8.5 or more. Semiconductor nanoparticle composite dispersion. (2) The SP value of the organic dispersion medium is 9.0 or more. The semiconductor nanoparticle composite dispersion liquid according to (1) above. (3) The organic dispersion medium is one or more mixed dispersion media selected from the group consisting of alcohols, ketones, esters, glycol ethers, and glycol ether esters. The semiconductor nanoparticle composite dispersion liquid according to (1) or (2) above. (4) The organic dispersion medium is one or more mixed dispersion media selected from acetone, PGMEA, PGME, IPA, ethanol, and methanol; The semiconductor nanoparticle composite dispersion liquid according to (1) or (2) above. (5) The organic dispersion medium is one or more mixed dispersion media selected from the group consisting of glycol ethers and glycol ether esters. The semiconductor nanoparticle composite dispersion liquid according to (1) or (2) above. (6) The organic dispersion medium is one or more mixed dispersion media selected from the group consisting of PGMEA and PGME; The semiconductor nanoparticle composite dispersion liquid according to (1) or (2) above. (7) The semiconductor nanoparticle composite dispersion has a fluorescence quantum efficiency of 80% or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (6) above. (8) The mass ratio of the aliphatic thiol ligand to the polar ligand (aliphatic thiol ligand / polar ligand) is 0.05 to 1.00. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (7) above. (9) The aliphatic thiol ligand has 6 to 14 carbon atoms. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (8) above. (10) The aliphatic thiol ligand is one or more of hexanethiol, octanethiol, and dodecanethiol. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (9) above. (11) The molecular weight of the polar ligand is 600 or less. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (10) above. (12) The molecular weight of the polar ligand is 450 or less. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (11) above. (13) The organic group of the polar ligand has at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an amino group, an ether bond, an ester bond, and a siloxane bond. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (12) above. (14) The organic group of the polar ligand has an ether bond. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (13) above. (15) The coordinating group of the polar ligand is a mercapto group or a carboxyl group. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (14) above. (16) The coordinating group of the polar ligand is a mercapto group. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (15) above. (17) The total mass fraction of the aliphatic thiol ligand and the polar ligand in the total surface ligands is 0.7 or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (16) above. (18) The total mass fraction of the aliphatic thiol ligand and the polar ligand in the total surface ligands is 0.8 or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (17) above. (19) The surface composition of the semiconductor nanoparticles contains Zn. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (18) above. (20) The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 80% or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (19) above. (21) The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 85% or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (20) above. (22) The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (21) above. (23) The half width of the emission spectrum of the semiconductor nanoparticle composite is 35 nm or less. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (22) above. (24) The semiconductor nanoparticles contain In and P. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (23) above. (25) The mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite dispersion liquid is 20 mass% or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (24) above. (26) The mass fraction of the semiconductor nanoparticles in the semiconductor nanoparticle composite dispersion liquid is 25 mass% or more. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (25) above. (27) The organic dispersion medium is a monomer or a prepolymer. The semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (26) above.
[0059] The semiconductor nanoparticle composite composition and the semiconductor nanoparticle composite cured film of the present invention can be produced by the following production method. (28) A method for producing a semiconductor nanoparticle composite composition, comprising the steps of: Adding either or both of a crosslinker and a dispersion medium to the semiconductor nanoparticle composite dispersion liquid according to any one of (1) to (27) above; Method for making semiconductor nanoparticle composite compositions. (29) A method for producing a semiconductor nanoparticle composite cured film, comprising the steps of: Curing the semiconductor nanoparticle composite composition obtained by the method for producing a semiconductor nanoparticle composite composition according to (28) above; Method for producing a semiconductor nanoparticle composite cured film.
[0060] The semiconductor nanoparticle composite of the present invention has the following configuration. <1> A semiconductor nanoparticle composite in which two or more types of ligands including an aliphatic thiol ligand and a polar ligand are coordinated to the surface of a semiconductor nanoparticle, the ligand comprises an organic group and a coordinating group; The aliphatic thiol ligand has an aliphatic hydrocarbon group as the organic group and a mercapto group as the coordinating group, The polar ligand comprises a hydrophilic functional group on the organic group, the mass ratio of the aliphatic thiol ligand to the polar ligand (aliphatic thiol ligand / polar ligand) is 0.05 to 1.00; Semiconductor nanoparticle composites. <2> The semiconductor nanoparticle composite is dispersible in an organic dispersion medium having an SP value of 8.5 or more. the above <1> The semiconductor nanoparticle composite according to claim 1. <3> The semiconductor nanoparticle composite is dispersible in an organic dispersion medium having an SP value of 9.0 or more. the above <1> or <2> The semiconductor nanoparticle composite according to claim 1. <4> The organic dispersion medium is one or more mixed dispersion media selected from the group consisting of alcohols, glycol ethers, and glycol ether esters. the above <2> or <3> The semiconductor nanoparticle composite according to claim 1. <5> The organic dispersion medium is one or more mixed dispersion media selected from the group consisting of acetone, PGMEA, PGME, IPA, ethanol, and methanol; the above <2> ~ <4> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <6> The aliphatic thiol ligand has 6 to 14 carbon atoms. the above <1> ~ <5> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <7> the aliphatic thiol ligand is one or more of hexanethiol, octanethiol, decanethiol, and dodecanethiol; the above <1> ~ <6> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <8> The molecular weight of the polar ligand is 600 or less. the above <1> ~ <7> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <9> The molecular weight of the polar ligand is 450 or less. the above <1> ~ <8> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <10> The total mass fraction of the aliphatic thiol ligand and the polar ligand in the total ligand is 0.7 or more. the above <1> ~ <9> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <11> The total mass fraction of the aliphatic thiol ligand and the polar ligand in the total ligand is 0.8 or more. the above <1> ~ <10> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <12> The organic group of the polar ligand has at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an amino group, an ether bond, an ester bond, and a siloxane bond; the above <1> ~ <11> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <13> the organic group of the polar ligand comprises an ether bond; the above <1> ~ <12> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <14> The coordinating group of the polar ligand is a mercapto group or a carboxyl group; the above <1> ~ <13> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <15> The coordinating group of the polar ligand is a mercapto group; the above <1> ~ <14> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <16> The semiconductor nanoparticle composite is dispersible in the organic dispersion medium, and the mass fraction of the semiconductor nanoparticles is 20 mass% or more. the above <2> ~ <15> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <17> The semiconductor nanoparticle composite is dispersible in the organic dispersion medium, and the mass fraction of the semiconductor nanoparticles is 25 mass% or more. the above <2> ~ <16> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <18> The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 80% or more. the above <1> ~ <17> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <19> The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 85% or more. the above <1> ~ <18> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <20> The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. the above <1> ~ <19> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <21> The semiconductor nanoparticle composite has an emission spectrum having a half-width of 35 nm or less. the above <1> ~ <20> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <22> The semiconductor nanoparticles comprise In and P; the above <1> ~ <21> The semiconductor nanoparticle composite according to any one of claims 1 to 4. <23> The semiconductor nanoparticles contain Zn on the surface of the semiconductor nanoparticles. the above <1> ~ <22> The semiconductor nanoparticle composite according to any one of claims 1 to 4.
[0061] The semiconductor nanoparticle composite dispersion of the present invention has the following configuration. <24> the above <1> ~ <23> 13. A semiconductor nanoparticle composite dispersion liquid in which the semiconductor nanoparticle composite according to any one of claims 1 to 12 is dispersed in an organic dispersion medium.
[0062] The semiconductor nanoparticle composite composition of the present invention has the following configuration. <25> the above <1> ~ <23> A semiconductor nanoparticle composite composition in which the semiconductor nanoparticle composite according to any one of claims 1 to 4 is dispersed in a dispersion medium, The dispersion medium is a monomer or a prepolymer. Semiconductor nanoparticle composite compositions.
[0063] The semiconductor nanoparticle composite cured film of the present invention has the following configuration. <26> the above <1> ~ <23> The semiconductor nanoparticle composite according to any one of claims 1 to 4 is dispersed in a polymer matrix. Semiconductor nanoparticle composite cured film.
[0064] It will be understood that the structures and / or methods described herein are presented as examples, and that numerous variations are possible, and that these specific examples or examples should not be taken in a limiting sense. A particular procedure or method described herein may represent one of many process methods. Thus, various acts illustrated and / or described may be performed in the order illustrated and / or described, or may be omitted. Similarly, the order of the methods described above may be altered. The subject matter of the present disclosure includes all novel and non-obvious combinations and subcombinations of the various methods, systems, and structures, as well as other features, functions, acts, and / or properties disclosed herein, and all equivalents thereof. EXAMPLES
[0065] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these.
[0066] [Example 1] An InP-based semiconductor nanoparticle composite was prepared according to the following method. (core) Indium acetate (0.3 mmol) and zinc oleate (0.6 mmol) were added to a mixture of oleic acid (0.9 mmol), 1-dodecanethiol (0.1 mmol), and octadecene (10 mL), and the mixture was heated to about 120°C under vacuum (<20 Pa) and reacted for 1 hour. The mixture reacted under vacuum was placed in a nitrogen atmosphere at 25°C, tris(trimethylsilyl)phosphine (0.2 mmol) was added, and the mixture was heated to about 300°C and reacted for 10 minutes. The reaction solution was cooled to 25°C, octanoic acid chloride (0.45 mmol) was poured in, and the mixture was heated at about 250°C for 30 minutes, and then cooled to 25°C to obtain a dispersion of InP-based semiconductor nanoparticles. These InP-based semiconductor nanoparticles were used as cores, and a shell was formed on the core surface as described below to produce core-shell type semiconductor nanoparticles, and the optical properties were measured.
[0067] (Shell precursor) In the preparation of the shell, first, the following precursors were prepared. <Preparation of Zn precursor solution> 40 mmol of zinc oleate and 75 mL of octadecene were mixed and heated at 110 °C for 1 hour under vacuum to prepare a Zn precursor with [Zn] = 0.4 M. <Preparation of Se precursor (trioctylphosphine selenide)> 22 mmol of selenium powder and 10 mL of trioctylphosphine were mixed in nitrogen and stirred until completely dissolved to obtain trioctylphosphine selenide with [Se] = 2.2 M. <Preparation of S precursor (trioctylphosphine sulfide)> 22 mmol of sulfur powder and 10 mL of trioctylphosphine were mixed in nitrogen and stirred until completely dissolved to obtain trioctylphosphine sulfide with [S] = 2.2 M. Using the precursors obtained as described above, a shell was formed on the surface of the InP-based semiconductor nanoparticles (core) as follows.
[0068] (Shell) The dispersion of the core was heated to 200 °C. At 200 °C, 0.75 mL of the Zn precursor solution and trioctylphosphine selenide (Se precursor) were simultaneously added and reacted for 30 minutes to form a ZnSe shell on the surface of the InP-based semiconductor nanoparticles. Furthermore, 1.5 mL of the Zn precursor solution and 0.6 mmol of trioctylphosphine sulfide (S precursor) were added, the temperature was raised to 250 °C and reacted for 1 hour to form a ZnS shell. The reaction solution of the semiconductor nanoparticles obtained by synthesis was added to acetone, mixed well and then centrifuged. The centrifugal acceleration was 4000 G. The precipitate was collected, normal hexane was added to the precipitate to prepare a dispersion. This operation was repeated several times to obtain purified semiconductor nanoparticles.
[0069] (Ligand) - Preparation of ligand alone - <Preparation method of PEG-SH> 210 g of methoxy PEG-OH (molecular weight 400) and 93 g of triethylamine were placed in a flask and dissolved in 420 mL of THF (tetrahydrofuran). The solution was cooled to 0 °C, and while taking care that the temperature of the reaction solution did not exceed 5 °C due to the heat of reaction, 51 g of methanesulfonyl chloride was gradually added dropwise under a nitrogen atmosphere. Then, the reaction solution was warmed to room temperature and stirred for 2 hours. This solution was extracted with a chloroform-aqueous system, and the organic phase was recovered. The obtained solution was dried over magnesium sulfate, the magnesium sulfate was removed by filtration, and then the filtrate was concentrated by evaporation to obtain an oily intermediate. This was transferred to another flask, and 400 mL of 1.3 M aqueous thiourea solution was added under a nitrogen atmosphere. After the solution was refluxed for 2 hours, 21 g of NaOH was added, and reflux was continued for another 1.5 hours. The reaction solution was cooled to room temperature, and 1 M aqueous HCl solution was added until pH = 7 to neutralize it. The obtained solution was extracted with a chloroform-aqueous system to obtain the target ligand (PEG-SH, molecular weight 400).
[0070] <Method for Preparing N-Acetyl N-(2-mercaptoethyl)propanamide> 1.2 g (10 mmol) of N-(2-sulfanylethyl)acetamide and 1.7 mL (12 mmol) of triethylamine were placed in a 100 mL round-bottom flask and dissolved in 30 mL of dehydrated dichloromethane. The solution was cooled to 0 °C, and 0.87 mL (10 mmol) of propanoyl chloride was slowly added dropwise under a nitrogen atmosphere while taking care that the temperature of the solution did not exceed 5 °C. After the addition was complete, the reaction solution was warmed to room temperature and stirred for 2 hours. The reaction solution was filtered, and the filtrate was diluted with chloroform. The solution was extracted in the order of 10% aqueous HCl solution, 10% aqueous Na2CO3 solution, and saturated aqueous NaCl solution, and the organic phase was recovered. After the organic phase was concentrated by evaporation, it was purified by column chromatography using a hexane-ethyl acetate mixed solvent as the developing solvent to obtain the target product.
[0071] <Method for Preparing PEG-COOH> Methoxy PEG-OH (molecular weight 350, 15 g) was dissolved in toluene (100 mL) at 60 °C, 4.2 g of potassium tert-butoxide was added, and the mixture was reacted for 6 hours. Then, 5.5 g of ethyl bromoacetate was added to the mixture, and the hydroxyl group in PEG was protected by an ethyl acetate group. The mixture was filtered, and the filtrate was precipitated in diethyl ether. The precipitate was dissolved in 1 M NaOH solution (40 mL), NaCl (10 g) was added, and the mixture was stirred at room temperature for 1 hour to remove the terminal ethyl group of PEG. This solution was adjusted to pH 3.0 by the addition of 6 M HCl. The resulting solution was extracted with a chloroform-water system to obtain PEG-COOH with a molecular weight of 400.
[0072] By changing methoxy PEG-OH (molecular weight 350, 15 g) to methoxy PEG-OH (molecular weight 550, 21 g) and performing the preparation in the same manner as above, PEG-COOH with a molecular weight of 600 was obtained. By changing methoxy PEG-OH (molecular weight 350, 15 g) to methoxy PEG-OH (molecular weight 700, 26 g) and performing the preparation in the same manner as above, PEG-COOH with a molecular weight of 700 was obtained. By changing methoxy PEG-OH (molecular weight 350, 15 g) to methoxy PEG-OH (molecular weight 950, 36 g) and performing the preparation in the same manner as above, PEG-COOH with a molecular weight of 1000 was obtained.
[0073] <Preparation method of TBP-S> Under a nitrogen atmosphere, 3.2 g of sulfur was placed in a flask, 25 mL of tributylphosphine was added, and the mixture was stirred overnight to obtain TBP-S.
[0074] <Preparation method of TOP-S> Under a nitrogen atmosphere, 3.2 g of sulfur was placed in a flask, 50 mL of trioctylphosphine was added, and the mixture was stirred overnight to obtain TOP-S.
[0075] (Preparation of semiconductor nanoparticle composite) In a flask, the purified semiconductor nanoparticles were dispersed in 1-octadecene to prepare a semiconductor nanoparticle 1-octadecene dispersion liquid. 10.0 g of the prepared semiconductor nanoparticle 1-octadecene dispersion liquid was placed in a flask, 0.2 g of dodecanethiol (DDT) was added as an aliphatic thiol ligand, and 4 g of PEG-SH was added as a polar ligand. The mixture was stirred at 110°C for 60 minutes under a nitrogen atmosphere, and cooled to 25°C to obtain a semiconductor nanoparticle composite. The reaction solution containing the semiconductor nanoparticle composite was transferred to a centrifuge tube and centrifuged at 4000G for 20 minutes, resulting in separation into a transparent 1-octadecene phase and a semiconductor nanoparticle composite phase. The 1-octadecene phase was removed, and the remaining semiconductor nanoparticle composite phase was collected. 5.0 mL of acetone was added to the obtained semiconductor nanoparticle composite phase to prepare a dispersion. 50 mL of normal hexane was added to the obtained dispersion, and the mixture was centrifuged at 4000 G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite.
[0076] (Optical property measurement of semiconductor nanoparticle composites) The optical properties of the semiconductor nanoparticle composite were measured using a fluorescence quantum efficiency measurement system (QE-2100, manufactured by Otsuka Electronics). The obtained semiconductor nanoparticle composite was dispersed in a dispersion medium, and a single light of 450 nm was applied to obtain an emission spectrum. The fluorescence quantum efficiency (QY) and full width at half maximum (FWHM) were calculated from the emission spectrum after re-excitation correction, which was obtained by removing the re-excitation fluorescence emission spectrum of the fluorescence emitted by re-excitation from the obtained emission spectrum. PGMEA was used as the dispersion medium.
[0077] (Dispersibility test of semiconductor nanoparticle composites) The purified semiconductor nanoparticle composite was heated to 550°C by differential thermogravimetry (DTA-TG), held for 10 minutes, and cooled. The residual mass after analysis was taken as the mass of the semiconductor nanoparticles, and the mass ratio of the semiconductor nanoparticles in the semiconductor nanoparticle composite was confirmed from this value. With reference to the above mass ratio, an organic dispersion medium was added to the semiconductor nanoparticle composite so that the mass fraction of the semiconductor nanoparticles was 20 mass%, and the dispersion state at that time was confirmed. Those that were dispersed were marked with an ◯, and those in which precipitation or turbidity was observed were marked with an ×, as shown in Tables 1-1 to 1-7. Table 2 shows the dispersion state when PGMEA was used as the organic dispersion medium and the mass fraction of the semiconductor nanoparticles was set to 20% by mass to 35% by mass. The results are indicated with an ◯ for those that were dispersed and an × for those in which precipitation or turbidity was observed. When two types of organic dispersion media were used as the dispersion medium, a mixed dispersion medium in a volume ratio of 1:1 was used.
[0078] The ligands coordinated to the semiconductor nanoparticles of the purified semiconductor nanoparticle complexes were measured using a nuclear magnetic resonance (NMR) device (JNM-LA400 manufactured by JEOL Ltd.) In all measurements, deuterated chloroform was used as the solvent, and tetramethylsilane was used as the internal standard substance for chemical shifts. Figure 1 shows the results of 1H-NMR measurement of the semiconductor nanoparticle composite prepared in Example 1. Signals were observed around 0.8 ppm to 2.5 ppm, 3.5 ppm to 4.0 ppm, and around 5.4 ppm. Figure 2 shows the 1H-NMR spectra of dodecanethiol, oleic acid, and PEG-SH. 1 and 2, it was found that the signals around 0.8 ppm to 2.5 ppm and around 5.4 ppm are caused by the alkyl group and carbon-carbon double bond of the aliphatic thiol ligand, respectively, and the signals around 3.5 ppm to 4.0 ppm are caused by the ether bond of the polar ligand. In other words, by adding up the signals of dodecanethiol, oleic acid, and PEG-SH, all of the signals obtained in the NMR spectrum of Example 1 can be explained without contradiction, and it is found that the semiconductor nanoparticle composite of Example 1 contains dodecanethiol, oleic acid, and PEG-SH as ligands. Furthermore, by comparing Figures 1 and 2, it can be seen that the signals around 0.8 ppm to 2.5 ppm belong to dodecanethiol and oleic acid, the signals around 3.5 ppm to 4.0 ppm belong to PEG-SH, and the signals around 5.4 ppm belong to oleic acid. From the area ratio of these signals, the abundance ratio of each ligand was calculated to be dodecanethiol:oleic acid:PEG-SH=8:3:89. In this way, the type and abundance ratio of the ligand can be determined from the position and peak area of each signal in the 1H-NMR spectrum.
[0079] Example 2 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 4.0 g of PEG-SH was used as the polar ligand in the step of preparing the semiconductor nanoparticle composite.
[0080] Example 3 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 1.0 g of dodecanethiol was used as the aliphatic thiol ligand, 1.5 g of PEG-SH was used as the polar ligand, and 0.5 g of oleic acid was further added.
[0081] Example 4 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 1.0 g of dodecanethiol was used as the aliphatic thiol ligand, 1.5 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand, and 0.5 g of oleic acid was further added.
[0082] Example 5 In the process of preparing the semiconductor nanoparticle composite, 0.3 g of dodecanethiol and 0.2 g of hexanethiol were used as the aliphatic thiol ligands, and further, 4.0 g of PEG-SH was used as the polar ligand, and a semiconductor nanoparticle composite was obtained in the same manner as in Example 1.
[0083] Example 6 In the process of preparing the semiconductor nanoparticle composite, 0.2 g of dodecanethiol was used as the aliphatic thiol ligand, 1.5 g of triethylene glycol monomethyl thiol (TEG-SH) was used as the polar ligand, and 0.5 g of oleic acid was further added, in the same manner as in Example 1, to obtain a semiconductor nanoparticle composite.
[0084] Example 7 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that 0.5 g of octanethiol was used as the aliphatic thiol ligand and 4.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand in the process of preparing the semiconductor nanoparticle composite.
[0085] Example 8 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that 0.5 g of hexanethiol was used as the aliphatic thiol ligand and 4.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand in the process of preparing the semiconductor nanoparticle composite.
[0086] Example 9 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that 0.5 g of hexanethiol was used as the aliphatic thiol ligand and 4.0 g of PEG-SH was used as the polar ligand in the step of preparing the semiconductor nanoparticle composite.
[0087] Example 10 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 1.0 g of decanethiol was used as the aliphatic thiol ligand and 4.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand.
[0088] Example 11 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.2 g of dodecanethiol was used as the aliphatic thiol ligand and 6.0 g of PEG-COOH (molecular weight 400) was used as the polar ligand.
[0089] Example 12 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 2.0 g of methyl 3-mercaptopropionate was used as the polar ligand, and 0.5 g of oleic acid was further added.
[0090] Example 13 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 6.0 g of PEG-COOH (molecular weight 600) was used as the polar ligand in the step of preparing the semiconductor nanoparticle composite.
[0091] Example 14 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 7.5 g of PEG-COOH (molecular weight 750) was used as the polar ligand in the step of preparing the semiconductor nanoparticle composite.
[0092] Example 15 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 10.0 g of PEG-COOH (molecular weight 1000) was used as the polar ligand.
[0093] Example 16 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 4.0 g of PEG-SH was used as the polar ligand, and 1.5 g of oleic acid was further added.
[0094] Comparative Example 1 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, no aliphatic thiol ligand was added, 4.0 g of PEG-SH was used as a polar ligand, and 4.0 g of tributylphosphine (TBP) was also added.
[0095] Comparative Example 2 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, no aliphatic thiol ligand was added, 4.0 g of PEG-SH was used as a polar ligand, and 4.0 g of trioctylphosphine (TOP) was further added.
[0096] Comparative Example 3 In a flask, 1.0 g of the semiconductor nanoparticle composite purified in the same manner as in Example 1, 10 mL of isopropanol, and 4.0 g of PEG-SH were placed. The solution was stirred at 80°C for 180 minutes under a nitrogen atmosphere and cooled to 25°C. 50 mL of normal hexane was added to the reaction solution, and the mixture was centrifuged at 4000G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. 5.0 mL of acetone was added to the precipitate to prepare a dispersion. 50 mL of normal hexane was added to the obtained dispersion, and the mixture was centrifuged at 4000G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite.
[0097] Comparative Example 4 In the process of preparing the semiconductor nanoparticle composite, 2.0 g of dodecanethiol was used as an aliphatic thiol ligand, 1.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as a polar ligand, and 1.0 g of oleic acid was further added. Then, the mixture was stirred at 110°C for 60 minutes under a nitrogen atmosphere and cooled to 25°C. 5.0 mL of normal hexane was added to the reaction solution to prepare a dispersion. 50 mL of acetone was added to the obtained dispersion, and the mixture was centrifuged at 4000G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite. Since the semiconductor nanoparticle composite of Comparative Example 4 did not disperse in PGMEA, the optical properties were measured after dispersing it in normal hexane.
[0098] Comparative Example 5 A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that no aliphatic thiol was added in the process of preparing the semiconductor nanoparticle composite, and further, 4.0 g of PEG-SH was used as a polar ligand in the process of preparing the semiconductor nanoparticle composite, and 1.0 g of oleic acid was added.
[0099] The luminescence properties, ligand mass ratios, and dispersion states in the dispersion medium of the obtained semiconductor nanoparticle composites are shown in Tables 1-1 to 1-7.
[0100] The meanings of the abbreviations shown in Tables 1-1 to 1-7 are as follows: QY: Fluorescence quantum efficiency FWHM: Half-width of the emission spectrum QD: Semiconductor nanoparticles (quantum dots) DDT: Dodecanethiol Hex-SH: Hexanethiol Oct-SH: Octanethiol Dec-SH: Decanethiol OA: Oleic acid
[0101] [Table 1-1]
[0102] [Table 1-2]
[0103] [Table 1-3]
[0104] [Table 1-4]
[0105]
Table 1-5
[0106]
Table 1-6
[0107]
Table 1-7
[0108]
Table 2
Claims
1. A semiconductor nanoparticle composite in which two or more types of ligands including an aliphatic thiol ligand and a polar ligand are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The aliphatic thiol ligand has an aliphatic hydrocarbon group as the organic group and a mercapto group as the coordinating group, The polar ligand comprises a hydrophilic functional group on the organic group, the hydrophilic functional group includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an amino group, an ether bond, an ester bond, and a siloxane bond; the mass ratio of the aliphatic thiol ligand to the polar ligand (aliphatic thiol ligand / polar ligand) is 0.05 to 1.00; Semiconductor nanoparticle composites.
2. The aliphatic thiol ligand has 6 to 14 carbon atoms. The semiconductor nanoparticle composite of claim 1 .
3. The molecular weight of the polar ligand is 600 or less. The semiconductor nanoparticle composite according to claim 1 or 2.
4. The total mass fraction of the aliphatic thiol ligand and the polar ligand in the total ligand is 0.7 or more. The semiconductor nanoparticle composite according to any one of claims 1 to 3.
5. the organic group of the polar ligand comprises an ether bond; The semiconductor nanoparticle composite according to any one of claims 1 to 4.
6. The coordinating group of the polar ligand is a mercapto group; The semiconductor nanoparticle composite according to any one of claims 1 to 5.
7. The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 80% or more. The semiconductor nanoparticle composite according to any one of claims 1 to 6.
8. The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. The semiconductor nanoparticle composite according to any one of claims 1 to 7.
9. The semiconductor nanoparticles include In and P; The semiconductor nanoparticle composite according to any one of claims 1 to 8.
10. A semiconductor nanoparticle composite dispersion liquid in which the semiconductor nanoparticle composite according to any one of claims 1 to 9 is dispersed in an organic dispersion medium.
11. A semiconductor nanoparticle composite composition in which the semiconductor nanoparticle composite according to any one of claims 1 to 9 is dispersed in a dispersion medium, The dispersion medium is a monomer or a prepolymer. Semiconductor nanoparticle composite compositions.
12. The semiconductor nanoparticle composite according to any one of claims 1 to 9 is dispersed in a polymer matrix. Semiconductor nanoparticle composite cured film.
Citation Information
Patent Citations
Fluorescent body, wavelength converting member and light-emitting device
JP2015086284A
Luminous body, light emitting film, light emitting diode, and light emitting device having luminous body
JP2019073705A
Acid stabilization of quantum dot-resin concentrates and premixes
WO2018226654A1
Quantum dot architectures for color filter applications
WO2019008374A1
Titanium compound containing quantum dots and production method, and photoelectric conversion element using the titanium compound containing quantum dots
JP2013136498A